Simulation of loading and unloading system to decrease staying and waiting times of arrived-in trucks in Esfahan Steel Company. (2015) - Sajadi, Seyed Mojtaba; Ghandehari, Mahsa; Abootalebian, Nader
This study aims at investigating the possible economical solutions to reduce the waiting times of the trucks that enter to factory to load the final products. To do so, the simulation of the system which is under study will be used. According to the recording time in the release and storage information of the factory's system, loading lines were the most time consuming sections, as a result this study focused on the existing lines. The study begins with timing the docks and different stations to access the system's factors which are under study. To simulate the system, ARENA 14 software was used. After validating the proposed model and confirming its validation, scenarios will be made in order to remove the obstacles while the trucks are loaded. Finally, some scenarios that decrease the trucks' wait time significantly were compared and prioritise among most economical solutions will be presented.